Lake water Secchi disk depth - Aaron F Diefendorf; Watts Dietrich; Hans H Naake; Thomas V Lowell; Megan C Corcoran (PANGAEA, 2025)
Diatom-derived highly branched isoprenoids (HBIs) are found extensively in marine sediments, but are observed in a limited number of lake sediments. To expand on this record, between 2022 and 2024, we collected lake surface sediment samples from 50 lakes in the United States of America from the Midwest and Northeast. Studied lakes capture a range in climate, water chemistry (e.g., pH, salinity, alkalinity), size, and trophic states. As part of this survey, we measured Secchi disk depth using a 30 cm diameter black and white disc. Weather conditions and time of day were variable and therefore these values should be considered minimum values.
In: Diefendorf, AF et al. (2025): Diatom-derived highly branched isoprenoids in lake waters and sediments [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.979496